A CRITICAL APPRAISAL ON VARIOUS SAMSKARAS WITH THEIR SCIENTIFIC AND MEDICAL IMPORTANCE IN PEDIATRIC AGE GROUP - Kumar, Shobhit (International Journal of Ayurveda and Pharma Research, 2017)
Samskaras are also known as cultural ceremonies. Samskaras are important cultural events in an individuals life right from the conception to death. These cultural events not only possess socio-cultural importance, but these also have great medical importance. Its important to know about timing, procedure and importance of these Samskaras. Important Samskaras in ones life includes Garbha Dharan Samskara, Jatakarma Samskara, Niskramana Samskara, Upveshan Samskara, Karnvedhan Samskara, Phalaprashan Samskara, Annaprashan Samskara, Swarnaprashana, Vedarambha Samskara.Garbha Samskara is a method for a worth full child, to endow future generations with good health, noble quality and high intelligence by improving the innate quality of mankind. Samskaras like Nishakraman, Upveshan, Suryadarsan and Chandra Darshana work as an important tool of assessment of growth and development in children at different ages. Samskaras like Karnavedha enhances child immunity. Swarnaprashan helps in better intellectual growth and improved immunity. Phalaprashan and Annaprashan provide essential nutrients in the form of micro and macronutrients to the child. These cultural events also enhance child growth and development. Aksharlekhan or Vedarambha Samskara has great importance in child personality development. These cultural events also have scientific validity and proved medical importance. So its need of hour that, one should understand the importance of these cultural event and make peoples aware regarding positive effects of various Samskaras.